Effect of Dexmedetomidine-Assisted Intravenous Anesthesia on Gastrointestinal Motility in Colon Cancer Patients After Open Colectomy - Ou, Chaopeng; Kang, Shiyang; Xue, Ruifeng; Lai, Jielan; Zhang, Yingjun (Frontiers in Surgery, 2022)
Background To explore the effect of dexmedetomidine (Dex)-assisted intravenous anesthesia on gastrointestinal motility in patients with colon cancer (CC) after open colectomy. Methods A total of 102 patients with CC, undergoing open colectomy in our hospital from January 2018 to January 2020, were selected and randomly divided into an observation group (n = 51) and a control group (n = 51). The patients in the control group received a routine combination of intravenous and inhalation anesthesia (CIIA), while those in the observation group received a Dex-assisted CIIA. The systolic blood pressure (SBP), the diastolic blood pressure (DBP), heart rate (HR), and the mean arterial pressure (MAP) were compared at different time points between the two groups. In addition, the intraoperative general conditions, the dosage of anesthetics, and the recovery of gastrointestinal functions were also compared between the two groups. Moreover, before operation and at 24 h after operation, the levels of serum gastrin (GAS) and plasma motilin (MTL) were detected by radioimmunoassay, and the level of plasma cholecystokinin (CCK) was detected by an enzyme-linked immunosorbent assay. The incidence of gastrointestinal complications was recorded in both groups. Results At T1-T3, the HR, SBP, DBP, and MAP levels were lower in both groups than those at T0. In addition, they were also lower in the observation group than those in the control group, showing significant differences (p < 0.05). The dosage of propofol and remifentanil in the observation group was lower than that in the control group, and there was a significant difference (p < 0.05). In the observation group, the postoperative first exhaust time, first defecation time, first ambulation time, and first feeding time were all earlier than those in the control group with significant differences (p < 0.05). After the operation, the observation group had higher levels of GAS and MTL but a lower level of CCK than the control group, and the differences were significant (p < 0.05). The incidence rate of gastrointestinal complications in the observation group (7.04%) was lower than that in the control group (19.61%), and there was a significant difference (χ2 = 4.346, p < 0.05). Conclusions Dex-assisted intravenous anesthesia can facilitate the recovery of gastrointestinal motility, can regulate the levels of gastrointestinal hormones, and can stabilize the levels of hemodynamic indexes in patients with CC after open colectomy.